INFLUENCE OF EMOTIONAL INTELLIGENCE ON COACHING EFFICACY EXPECTATIONS AMONG FOOTBALL COACHES - Tatiana Iancheva; Gancho Prodanov (Scientific Publishing House. NSA Press, 2018)
Coaches' confidence in their coaching abilities has a great influence on athletes and the results from their activity. In an attempt to explain coaching efficacy some authors relate it to emotional intelligence. The aim of the present research is to study the interdependence between emotional intelligence and coaching efficacy among football coaches. Methodology: The research was done among 50 football coaches aged between 23 and 45 years with different level of qualification. In order to fulfill the aim, we used: 1) Background information; 2) Coaching Efficacy Scale (CES; Feltz et al., 1999); 3) Emotional Intelligence Scale (EIS; Schutte et al., 1998). Results: the results reveal that the leading subscales for the researched football coaches are "Technique efficacy" and "Motivation efficacy". We established significant correlations among the subscales of emotional intelligence and coaching efficacy. The results show a significant influence of emotional intelligence on coaching efficacy expectations. High Emotional Intelligence leads to increase in Technique efficacy. Conclusions: Our results regarding coaching efficacy reveal a certain specificity in comparison with the data published by foreign authors but confirm the findings in literature about the role of emotional intelligence as a predictor of coaching efficacy.